Behavioral Improvements and its Molecular Mechanism of Ilex kudingcha C.J. Tseng on Animal Model of Alzheimer’s Disease - Lap Thi Nguyen; Nguyen Huu Son; Tran Nguyen Hong; Nguyen Minh Khoi; Kinzo Matsumoto; William R. Folk; Masamitsu Yamaguchi; Pham Thi Nguyet Hang (Faculty of Pharmacy, Universitas Gadjah Mada, 2020)
Alzheimer's disease (AD) is a common chronic neurodegenerative disease with well-defined pathophysiological mechanisms. Ilex kudingcha (IK) C.J. Tseng is commonly known as bitter tea or “Khom” tea in Vietnam. The present study was conducted to investigate the anti-dementia effect of IK using olfactory bulbectomized (OBX) mice. OBX mice were daily treated with IK extract (540 mg/kg) or reference drug, tacrine (2.5 mg/kg) 1 week before and continuously for 3 days after the OBX surgery. The object recognition test, modified Y maze test and fear conditioning test were employed to analyze non-spatial short-term, spatial short-term and long-term memories of the mice respectively. Administration of IK extract and tacrine attenuated these OBX-induced cognitive deficits in mice. The effects of IK and tacrine on spatial short-term memory impairment were reversed by scopolamine, a muscarinic receptor antagonist. The amyloid-beta (Aβ) production in adult transgenic Drosophila brain flies was also investigated by using Western blotting with APP-HA antibody. These results indicated that IK extract improves short-term and long-term memory disturbances in OBX mice and that muscarinic receptor may play a role on these actions. In addition, our result also showed that IK extract reduces the expression of amyloid precursor protein (APP) in brain of AD model using Drosophila melanogaster.